2017
DOI: 10.1515/mgr-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

The importance of on-site evaluation for placing renewable energy in the landscape: A case study of the Búrfell wind farm (Iceland)

Abstract: Using a case study of the Búrfell wind farm project, a large wind farm proposed in the Central

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…These findings have led to the growing importance of spatial planning and consideration of environmental and social impacts. Some research projects are concerned with the optimisation of wind farms and the visualisation of wind turbines and their effects on ecosystems and nature conservation [10]. However, those approaches must not be confused with broad-based scenario-building and the inclusion of nature conservation as a criterion.…”
Section: Introductionmentioning
confidence: 99%
“…These findings have led to the growing importance of spatial planning and consideration of environmental and social impacts. Some research projects are concerned with the optimisation of wind farms and the visualisation of wind turbines and their effects on ecosystems and nature conservation [10]. However, those approaches must not be confused with broad-based scenario-building and the inclusion of nature conservation as a criterion.…”
Section: Introductionmentioning
confidence: 99%
“…It is easy to anticipate a clash with the prevailing nature imaginary. Negotiating this new terrain will require new and sensitive methods for the evaluation of local impacts (Frantál et al, 2017).…”
Section: Conclusion: Imagining Energy Futuresmentioning
confidence: 99%
“…For example, a case study on local planning of WE in Sweden showed that the processes often include governmental actors but exclude others (Gustafsson et al, 2015). A study of Frantál et al (2017) about wind farms in Iceland showed that new methods like mental mapping could be beneficially utilized to involve various actors in the WE planning processes.…”
Section: Local Planningmentioning
confidence: 99%